CELLULAR IMMUNITY INDICATORS IN NEWBORNS WITH HEMOLYTIC DISEASE UNDERGOING HIGH-TECH FETAL SURGERY - У. Джабборов; К. Хаматов (Неонатологія, хірургія та перинатальна медицина)
One of the most serious complications of pregnancy in women is fetal and neonatal hemolytic disease, which develops as a result of the breakdown of red blood cells in the fetus under the influence of maternal anti-Rhesus antibodies.